Poster 227: Correlations among Patient Reported Mental Health Scores and Functional Outcomes after Osteochondral Allograft Transplantation in the Knee. Issue 7 (30th July 2022) - Williams, Jonathan; Rucinski, Kylee; Stucky, Renee; Nuelle, Clayton; Stannard, James; Cook, James
Objectives: To use prospectively collected registry data to examine the relationships among self-reported mental health scores and functional outcomes after osteochondral allograft (OCA) transplantation in the knee. The study hypothesis was that Patient-reported Outcomes Measurement Information System (PROMIS) Mental Health scores would strongly correlate with patient-reported pain and function scores, as well as with failure of functional graft survival after OCA transplantation in the knee. Methods: With IRB approval and informed consent, patients undergoing OCA transplantation in the knee were enrolled in a lifelong comprehensive outcomes registry. Patients with large (>4cm 2 ) shell-graft OCA transplants and complete 2-year outcomes data for patient-reported IKDC subjective knee evaluation, VAS Pain, SANE, PROMIS Physical Function, and PROMIS Mental Health measures for pre-operative, 1-year, and 2-year postoperative time points were analyzed. Patients who required OCA revision surgery or total knee arthroplasty within the study period were defined as graft failures. Pearson's correlations analyses were used to examine strength of relationships among patient reported outcomes scores at each time point and for change in scores between time points. General logistic regression models were used to analyze associations between PROMIS Mental Health scores and graft failure. Statistical significance was defined a priori as p<0.05. Results: A total of 299 patients met criteria for inclusion. Across time points, PROMIS Mental Health scores were found to be moderately correlated with IKDC (r 2 = 0.42) and PROMIS Physical Function scores (r 2 = 0.43), and weakly correlated with Pain (r 2 = 0.27) and SANE scores (r 2 = 0.34). One-year PROMIS Mental Health improvement scores were found to be weakly correlated with one-year IKDC (r 2 = 0.2), SANE (r 2 = 0.27), and PROMIS Physical Function improvement scores (r 2 = 0.3). Two-year PROMIS Mental Health scores were found to be moderately correlated with two-year SANE improvement scores (r 2 = 0.42). Preoperative PROMIS Mental Health was significantly (p=0.006) associated with graft failure, while PROMIS Mental Health improvement scores were not (p>0.48). Conclusions: Self-reported mental health was more strongly correlated with measures of function than measures of pain for patients undergoing OCA transplantation in the knee. Importantly, the data also indicated a significant association for self-reported mental health at baseline with graft failure during the first two years after OCA transplantation, while changes in mental health score were not significantly associated with graft failure. Taken together, the results of this study suggest that assessment of patients' mental health prior to osteochondral allograft transplantation knee surgery can provide valuable information to patients and healthcare providers with respect to their clinical outcomes.